Towards a Pan-African Kiswahili: Strategies for Linguistic Expansion and Continental Integration - Victor Mpoyo Kalume; Prospery Mwansa Mwila (Journal of Education and Teacher Training Innovation, 2025)
Kiswahili is one of Africa’s most widely spoken indigenous languages and holds growing significance as a symbol and instrument of Pan-African integration. Spoken by more than 200 million people and recently recognized as a Continental Working Language of the African Union, Kiswahili possesses unique potential to facilitate political cooperation, socio-economic development, and cultural unity across Africa. This study examines evidence-based strategies for the sustainable expansion of Kiswahili beyond its traditional East African stronghold to the wider continent. Employing a qualitative systematic literature review guided by the PRISMA framework, the paper synthesizes scholarly research, language policy documents, and regional integration frameworks related to language planning, education, digital media, and Pan-Africanism. The findings identify six interconnected pillars essential for Kiswahili’s continental growth: legal and policy recognition, education and teacher training, curriculum harmonization, media and digital dissemination, cultural diplomacy, and economic integration. While East Africa demonstrates high levels of institutionalization and everyday use, Central and Southern Africa show growing adoption through education and media, and West and North Africa remain in early stages of engagement. Persistent challenges include the dominance of colonial languages, shortages of trained teachers, uneven digital infrastructure, and concerns over linguistic diversity. The study argues that Kiswahili should be promoted as a complementary African lingua franca rather than a replacement for indigenous languages. The paper concludes that coordinated political commitment, sustained investment, and Pan-African institutional collaboration are necessary to position Kiswahili as a functional, modern, and unifying language capable of advancing Africa’s integration agenda and cultural renaissance.